Penerapan Model Pembelajaran Radec untuk Melejitkan Pembelajaran IPS di Sd - Denny Ramadhan; Wahyu Sopandi; Arie Rakhmat Riyadi; Neni Maulidah (Journal of Practice Learning and Educational Development, 2025)
This study aims to describe the implementation of the RADEC learning model in enhancing 21st-century skills in the Social Studies (IPS) subject at elementary schools. The research employed a pre-experimental design with a one-group pretest-posttest approach involving fifth-grade students at a public elementary school in Bandung City. The RADEC model was implemented through the stages of Read, Answer, Discuss, Explain, and Create, designed to develop students' critical thinking, communication, collaboration, and creativity skills. At the Create stage, the philosophy of positivism serves as an important foundation, where students are encouraged to create works based on empirical observation so that the results are not only innovative but also objectively testable. The results showed a significant improvement in student abilities, with the average score increasing from 60.17 (pre-test) to 85.67 (post-test), and the percentage of students achieving the Minimum Mastery Criteria (KKM) rising from 33.3% to 93.3%. These findings affirm that the RADEC model integrated with the positivist approach can encourage students to actively create real solutions in the context of elementary school Social Studies learning.